PREPARED FOR INTERNATIONAL SCHOOL: VIEWED FROM TEACHERS’READINESS OF BRAWIJAYA SMART SCHOOL MALANG - Leil Badrah Zaki; Adila Jefiza (Universitas Negeri Padang, 2017)
This research aims to discuss teachers’ readiness to face the challenge of international school that will be defined from their background knowledge of international school itself, the qualification and competence of the teachers and also teachers’ attitude toward this change. The subjects of the study are teachers from Brawijaya Smart School since the school has already begun to conduct teachers’ training specifically English for classroom instruction that is guided by Direct English Malang. The teachers are consisted of 6 pre-school teachers, 29 elementary school teachers, 27 junior high school teachers and 45 senior high school teachers. The prior research toward the teacher qualification was conducted through English placement test. The data of the teacher placement test show that 90% Elementary teacher is in basic level and 10 % of them is in intermediate level, 75% of Junior high school teacher is in basic level and 25 % of them is in intermediate level. 78% Senior high school teacher is in basic level, 20% of them is in intermediate level and only 0, 03% of them is advanced. The result of the present study could become a recommendation from teachers’ view for the school principle and decision maker of Brawijaya Smart School in conducting a further teacher training in preparing to become international school.